Building new institutional capacity of Polish cities - Miszczak, Katarzyna (Budowanie nowej zdolności instytucjonalnej polskich miast, 2019)
The article presents selected issues related to building the institutional capacity of Polish cities in light of contemporary challenges in the field of urban renewal and improving the quality of urban space based on attracting human, social and creative capital. The research purpose is the identification and characterization of the main features and problems of the functioning of the urban institutional system in Polish realities, in which the integrated territorial approach, participation and effective implementation of learning processes should constitute the essential elements of the innovative institutional potential of urbanized units. One of the important research findings presented in the article is the statement that strengthening the institutional capacity of Polish cities by building different organizational forms, characterized by decentralization, multifaceted management, networking, innovation, creativity and an eco-friendly approach, sets the framework for a new urbanity
Biblioteka Regionalisty, 2019, Nr 19, s. 130-145
Keywords: Dolny Śląsk